The utilization of e-books and video media in the tradition of food abstinence among postpartum - Hendryani, Deasy; Dewi Mayangsari; Retno Apriliyanti; Sa'adah Mujahidah (Link Journal of Nursing, 2024)
Introduction: The puerperium is a precarious phase due to the problems that arise. This scenario can be averted by ensuring proper nourishment. Nutritional deficiencies are frequently observed in postpartum women due to mother abstinence and cultural practices. Abstinence behavior can be modified through health education. Objective: To assess the impact of e-book and video instruction on the attitudes toward abstinence traditions among postpartum women at Puskesmas Kandeman, Batang Regency. Methods: quasi-experimental research utilizing a one-group pretest-posttest methodology. The sample comprised 16 postpartum mothers from the Kandeman Health Centre region in Batang Regency, selected using purposive sampling. The research instruments included questionnaires, films, pamphlets, and standard operating procedures (SOPs). Data analysis employing the paired t-test. Results: The mean attitude towards abstinence tradition was 45.25 before providing e-book and video education and increased to 59.5 afterward. The e-book and video instruction significantly influence the attitude towards abstinence tradition among postpartum women at Puskesmas Kandeman, Batang Regency (r: 0.000). Conclusion: Using e-books and movies in education influences the modification of attitudes towards the abstinence tradition.